Designer microparticles produced from glass microfluidic devices for drug delivery - Ekanem Ekanem; Goran Vladisavljevic (2015)
Methods for the manufacture of monodispersed emulsions which serve as templates for the production of microspheres used in drug encapsulation are being increasingly explored. This is due to the fact that such uniform emulsions, which are more stable, bring about microparticles which possess higher drug encapsulation efficiencies and more predictable release profiles. In this work, 3D (axisymmetric) flow focusing glass capillary microfluidic devices, pioneered by Utada et al. (2005), have been used for the generation of monodispersed emulsion droplets. These emulsions served as precursors for the production of microspheres with varying controllable surface and internal microstructure. Unique video images of droplet generation and microstructural images of microparticles together with drug release profiles from produced particles were obtained and would be presented.